Sistem Pengambilan Pekerja secara di atas talian (RMS) - Mansor, Nurul Janah; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2022)
: In this day and age, applying for a job and recruiting a job is easy because everything is at our fingertips. This is because, with the advent of gadget technology and smartphones with Internet data, all applications can be completed online, which makes it easier for people to find jobs. The sophistication of information technology nowadays has had a lot of positive impact on society, especially in job advertising. Indirectly, this can save costs and time for a company in the process of recruiting new employees. At the same time, employees can also find out about vacancies in a company by checking the website. However, there are already too many online job search applications being developed but not all applications provide complete modules. Therefore, the construction of an online Recruitment System (E-job) was developed to provide a complete system that provides modules for uploading resumes, examination modules, registration and login modules, selecting dates for interviews, job search modules and report modules. The proposed system uses Adobe Macromedia Dreamweaver version 6 software to design the system with the help of PhpMyAdmin software version 7.7 for use in storing data to the database. It is hoped that this system will be successfully developed and will be able to facilitate the recruitment of employees.